Plant-mediated and nonadditive effects of two global change drivers on an insect herbivore community - Sassi, Claudio de; Lewis, O.T; Tylianakis, Jason M. (Wiley, 2012)
Warmer temperatures can alter the phenology and distribution of individual species. However, differences across species may blur community‐level phenological responses to climate or cause biotic homogenization by consistently favoring certain taxa. Additionally, the response of insect communities to climate will be subject to plant‐mediated effects, which may or may not overshadow the direct effect of rising temperatures on insects. Finally, recent evidence for the importance of interaction effects between global change drivers suggests that phenological responses of communities to climate may be altered by other drivers. We used a natural temperature gradient (generated by elevation and topology), combined with experimental nitrogen fertilization, to investigate the effects of elevated temperature and globally increasing anthropogenic nitrogen deposition on the structure and phenology of a seminatural grassland herbivore assemblage (lepidopteran insects).We found that both drivers, alone and in combination, severely altered how the relative abundance and composition of species changed through time. Importantly, warmer temperatures were associated with biotic homogenization, such that herbivore assemblages in the warmest plots had more similar species composition than those in intermediate or cool plots. Changes in herbivore composition and abundance were largely mediated by changes in the plant community, with increased nonnative grass cover under high treatment levels being the strongest determinant of herbivore abundance. In addition to compositional changes, total herbivore biomass more than doubled under elevated nitrogen and increased more than fourfold with temperature, bearing important functional implications for herbivores as consumers and as a prey resource. The crucial role of nonnative plant dominance in mediating responses of herbivores to change, combined with the frequent nonadditive (positive and negative) effects of the two drivers, and the differential responses of species, highlight that understanding complex ecosystem responses will benefit from multifactor, multitrophic experiments at community scales or larger.